NUMERICAL EVALUATION OF SCAR AFTER BREAST RECONSTRUCTION WITH ABDOMINAL ADVANCEMENT FLAP - Kovář, M; Čapek, L; Vítová, L; Molitor, M (Acta chirurgiae plasticae, 2016)
BACKGROUND: The treatment of breast cancer has developed a lot during the last decade, nevertheless it still remains a considerable social and economical problem all over the world. The choice of the surgical procedure depends on a patients protocol and the surgeons preferences. The aim of this study is to evaluate the stress on the scar after breast reconstruction. METHODS: Mathematical modeling of the sutured skin flap used for breast implant placement was divided into the following two steps. At first, material model of the selected silicone implant was identified. Afterwards, the mathematical model of the breast and implant was performed. RESULTS: Maximal geometrical deviation for anatomical and round implant is placed on the lower surface of the breast and upper surface of the breast, while in the area of lateral geometry and the area around the nipple the agreement reaches very high level. The maximal tension is located in two median stitches. The maximal force reaches 0.025 N. The Cauchy stress equivalent is located around the nipple and reaches the value of 380 kPa. CONCLUSION: From our results it can be seen, that the anatomical and round breast implants do not result in the same stress on the scar. The maximal value difference reaches 13.4% between stress values for these two breast implants and the round implant results in higher loaded scar compared to the anatomical implant.
Keywords: implantace prsní náhrady; Mammaplasty; finite element method; Breast Neoplasms; Breast Implantation; statistické modely; břicho; Breast Implants; silicone implant aesthetical surgery.; Abdomen; ženské pohlaví; Models, Statistical; Surgical Flaps; Humans; jizva; anatomické modely; Models, Anatomic; chirurgické laloky; nádory prsu; prsní implantáty; mamoplastika; Female; Scar; breast; Cicatrix; lidé